The Effect of In-Pipe Fluid States and Types on Axial Stiffness Characteristics of Fiber-Reinforced Flexible Pipes - Jingyue You; Yinglong Zhao; Ben Zhang (Journal of Marine Science and Engineering)
As critical components in marine engineering fluid transmission systems, fiber-reinforced flexible (FRF) pipes have static mechanical properties that depend on internal fluid pressure. Current analytical approaches predominantly employ uniformly distributed load (UDL) assumptions to simulate unidirectional fluid pressure effects on pipe surfaces. However, existing methodologies neglect fluid–pipe structure coupling effects. This study investigates the rubber-based FRF pipe by establishing a numerical model incorporating fluid–structure interaction effects and material nonlinearity, aiming to explore how different fluid states (closed or constant pressure) and fluid types (incompressible or compressible) influence the mechanical behavior of the FRF pipe under axial loading. Experimental validation of the numerical model demonstrates that UDL assumptions remain valid for gas-filled pipes (both in the closed and constant pressure states) and the liquid-filled pipe in the constant pressure state. The incompressibility of the filled liquid significantly enhances pipe axial stiffness, invalidating the UDL approximation method in liquid-filled closed states. Furthermore, the asymptotic saturation model proposed effectively quantifies the liquid-induced enhancement in axial stiffness. The developed numerical model and derived conclusions provide valuable insights into structural design optimization, experimental protocol development, and practical engineering applications for FRF pipes.